Network attack classification framework based on Autoencoder model and online stream analysis technology - Hung, Nguyen Viet; Mai, Dang Thi; Tung, Ngo Thanh (Journal of Science and Technology on Information security, 2023)
Abstract— To deal with diverse and constantly changing forms of cyberattacks, machine learning methods have been researched and applied extensively in network data processing for positive results in network attack detection. However, machine learning models require extensive computational resources and their application to handle significant real-time data flow monitoring problems still needs improvement. In this paper, we research and propose a network attack detection framework using a 2-stage classification algorithm with an Autoencoder model, integrating online stream processing technology based on Apache Kafka and Spark technology. The results show that the proposed framework has high efficiency in detecting network attacks and faster processing time than traditional data processing technology.